China's auto industry: regimes of production and industrial policy in the age of electric cars. (14th March 2023) - Lüthje, Boy; Wu, Dan; Zhao, Wei
This article discusses China's industrial and labour policy for the automotive industry facing the transition to the era of new energy vehicles. A conceptual framework on the regimes of production is employed to analyse the present transformation of industry structures in production models and labour markets. The growth of private-capitalist regimes of high-performance, low wages, and high profit incentives for workers is identified, which can be described as the 'Foxconnisation' of the industry, and it is at the expense of the corporate-bureaucratic regimes prevalent among the leading Sino-foreign joint ventures. As production networks become vertically disintegrated, some non-traditional industrial players are highlighted in the discussion of some recent developments in the industry during the ongoing COVID-19 pandemic. The profound transformation in the regimes of production brought about social contradictions related to the production process, and new challenges and implications for workplace policies. The empirical study of this article confirms the necessity of trade union strategies inside China from an international perspective in order to ensure social standards and a more sustainable green transformation of the industry.